2012
DOI: 10.1021/jp2105133
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Chemical Shielding Anisotropy to Probe Structure and Disorder in Ceramics: 89Y MAS NMR and First-Principles Calculations

Abstract: The local structure and cation disorder in Y2(Sn,Ti)2O7 pyrochlores, materials proposed for the encapsulation of lanthanide- and actinide-bearing radioactive waste, is investigated using 89Y (I = 1/2) NMR spectroscopy and, in particular, measurement of the 89Y anisotropic shielding. Although known to be a good probe of the local environment, information on the anisotropy of the shielding interaction is removed under magic angle spinning (MAS). Here, we consider the feasibility of experimental measurement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 57 publications
(97 reference statements)
3
75
0
Order By: Relevance
“…[31] Recent papers proved that 89 Y NMR spectroscopy is a useful probe for local ordering in solid-state compounds. [38][39][40][41] Consequently, we performed 13 (Figures 2 and 3) show no evidence of local ordering and support the interpretation of randomly distributed yttrium and lanthanum atoms. Figure 2 clearly shows that regardless of the lanthanum doping rate, the 89 Y NMR signal remains almost identical.…”
Section: Resultssupporting
confidence: 70%
“…[31] Recent papers proved that 89 Y NMR spectroscopy is a useful probe for local ordering in solid-state compounds. [38][39][40][41] Consequently, we performed 13 (Figures 2 and 3) show no evidence of local ordering and support the interpretation of randomly distributed yttrium and lanthanum atoms. Figure 2 clearly shows that regardless of the lanthanum doping rate, the 89 Y NMR signal remains almost identical.…”
Section: Resultssupporting
confidence: 70%
“…The 13 C CP CSA Amplification [39,40] spectrum of the BTA considered in this study is shown in Figure 7 each analyzed carbon environment is given by the 95% confidence interval as extracted from the rms deviation 2D contour plots shown in (e-g). [41,42,69] The parameters extracted at the minima of these 2D surfaces are given in Table 3 for the three sites of interest.…”
Section: Solution Studymentioning
confidence: 99%
“…With respect to the anisotropy of the shift interaction, methods have been introduced that are not only capable of recoupling the inhomogeneity averaged out by the fast mechanical rotation, but also amplifying it, as if the experiment was performed at a slower and fictitious spinning rate. [37][38][39][40][41][42] This allows for more precise measurements of the full shielding tensor than those that one can achieve under static conditions or by spinning the sample at lower rates. [38] With respect to the chemical shift interaction, the following convention of NMR parameters is adopted in this study: [43] …”
Section: Introductionmentioning
confidence: 99%
“…For nuclear sites that possess high local symmetry, resulting in small anisotropies, "amplification" experiments have also recently been developed [27], increasing the apparent magnitude of the interaction (by a user-defined scaling factor) and enabling more accurate measurement. The experiment used in this work, the CSA-amplified PASS approach [28,29], has been used successfully to investigate 1 H, 13 C, 31 P and 89 Y local environments in a range of materials, and correlations with local structural parameters, e.g., bond distances or point symmetry, demonstrated [29][30][31][32][33]. For ZIFs, solid-state NMR spectroscopy can provide information on the type and relative proportions of linkers present, and the number of crystallographically-distinct molecules present in the asymmetric unit.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are typically removed under the sample rotation used to achieve high resolution, they can be measured either from a slow MAS spectrum or from the sideband pattern in the indirect dimension of a two-dimensional experiment that recouples, or selectively reintroduces, the anisotropic shielding [26,27]. It has been shown that the anisotropic shielding, the asymmetry and the tensor orientation can provide information on the local structure including, e.g., bond distances and point symmetry [15,16,24,30]. Given the complexity of the 13 C spectra of most ZIFs, slow MAS experiments result in considerable spectral overlap, and CSA-amplified PASS experiments have been used to reintroduce and measure the anisotropic shielding.…”
mentioning
confidence: 99%